Influence of psychiatric symptom profiles of parents on sleep bruxism intensity of their children - Cumhur Korkmaz; İbrahim Berk Bellaz; Mehmet Ali Kılıçarslan; Sibel Dikicier; Barış Karabulut (Acta Odontologica Scandinavica)
Objective: The objective of this study was to evaluate the effects of parental anxiety, depression levels and psychiatric symptom profiles of parents on the occurrence of sleep bruxism in children.